Age‐associated alterations in corpus callosum white matter integrity in bipolar disorder assessed using probabilistic tractography. (22nd December 2014) - Toteja, Nitin; Guvenek‐Cokol, Perihan; Ikuta, Toshikazu; Kafantaris, Vivian; Peters, Bart D; Burdick, Katherine E; John, Majnu; Malhotra, Anil K; Szeszko, Philip R
<x xml:space="preserve">Abstract</x> Objectives Atypical age‐associated changes in white matter integrity may play a role in the neurobiology of bipolar disorder, but no studies have examined the major white matter tracts using nonlinear statistical modeling across a wide age range in this disorder. The goal of this study was to identify possible deviations in the typical pattern of age‐associated changes in white matter integrity in patients with bipolar disorder across the age range of 9–62 years. Methods Diffusion tensor imaging was performed in 57 (20 male and 37 female) patients with a diagnosis of bipolar disorder and 57 (20 male and 37 female) age‐ and sex‐matched healthy volunteers. Mean diffusivity and fractional anisotropy were computed for the genu and splenium of the corpus callosum, two projection tracts, and five association tracts using probabilistic tractography. Results Overall, patients had lower fractional anisotropy and higher mean diffusivity compared to healthy volunteers across all tracts (while controlling for the effects of age and age2). In addition, there were greater age‐associated increases in mean diffusivity in patients compared to healthy volunteers within the genu and splenium of the corpus callosum beginning in the second and third decades of life. Conclusions Our findings provide evidence for alterations in the typical pattern of white matter development in patients with bipolar disorder compared to healthy volunteers. Changes in white matter development within the corpus callosum may lead to altered inter‐hemispheric communication that is considered integral to the neurobiology of the disorder.